RELIGIOUS CONVERSIONS AND LEGAL PROVISIONS IN INDIA: AN ANALYSIS OF THE LEGISLATIVE FRAMEWORK - Narang, Inderpreet Kaur; Reema Chand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Religious conversions in India have been a subject of intense social, political, and legal debate, particularly in the context of the country’s pluralistic society and its constitutional guarantees of religious freedom. Over the years, conversion to non-Hindu religions, especially Christianity and Islam, has been viewed with concern by certain sections of society, who argue that conversions are often motivated by fraudulent means, coercion, or inducement. This has led to the enactment of Anti-Conversion laws in various Indian states, ostensibly aimed at regulating religious conversions and ensuring that they are voluntary and not conducted through coercive tactics. These laws, however, have generated significant controversy, with critics asserting that they undermine the constitutional right to freedom of religion and disproportionately target minority religious communities, particularly Christians and Muslims. This paper examines the socio-legal and political dynamics surrounding religious conversions and Anti-Conversion state legislations in India.